Reinterpreting Justice in Al-Farabi’s Political Philosophy: Relevance to Contemporary Islamic Human Rights Thought - Syukri; Adenan; Syahminan (MILRev: Metro Islamic Law Review, 2025)
This study critically explores Al-Farabi’s conception of justice in his political philosophy and evaluates its normative potential and conceptual limitations in the context of contemporary human rights discourse. The central research question investigates the extent to which Al-Farabi’s vision of the al-Madina al-Fadila (Virtuous City) can serve as a philosophical framework for bridging classical Islamic values with modern human rights principles. Rather than assuming full compatibility, the study interrogates the tension between Al-Farabi’s virtue-based, hierarchical model of justice and contemporary demands for equality, intersectional rights, and democratic participation. Employing a qualitative, library-based method and a philosophical hermeneutic approach, the research analyzes key texts—particularly Ara’ Ahl al-Madina al-Fadila and Tahsil al-Sa‘ada—alongside contemporary literature on Islamic legal reform and human rights theory. The findings demonstrate that Al-Farabi’s emphasis on rational leadership, ethical governance, and communal well-being—while historically bounded—offers interpretive value for rethinking legal reform through maqasid al-shari‘ah and contextual ijtihad. However, the study also underscores the epistemological challenges of adapting metaphysical frameworks to rights-based paradigms. It concludes that Al-Farabi’s thought should inspire—not dictate—Islamic legal innovation by contributing ethical and rational principles that remain critically grounded within both Islamic tradition and contemporary socio-legal realities. Academically, this research contributes to the growing body of interdisciplinary scholarship at the intersection of Islamic philosophy, political theory, and human rights, offering a nuanced reappraisal of classical Islamic thought as a dynamic resource for ethical-legal reform in pluralistic modern societies.